2021
DOI: 10.1088/1742-6596/1940/1/012095
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of real analysis module with PQ4R strategy in facilitating self-regulated learning (SRL)

Abstract: Students do not have teaching materials that suit their needs. the need for students to improve their learning outcomes, independent learning, and teaching materials that are easy to understand and structured according to the learning outcomes of FKIP students. Therefore the steps in the PQ4R strategy can help students in organizing texts, and organize itself to obtain more in-depth information by means of broader elaboration. So students will be more independent in learning. Independence in learning is termed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In neurological applications, CDMDs are used to simulate three complex learning activities, such as learning states under different supervision levels, learning states based on levels of interest, and the effect of preview and review on memory behaviors according to the PQ4R (Preview, Question, Read, Reflect, Recite, Review) strategy that has rarely been reported. [37][38][39] This work of doping CDs not only improves the electrical performance of memristors, but also facilitates the development of artificial neural systems. [40][41][42]…”
Section: Introductionmentioning
confidence: 99%
“…In neurological applications, CDMDs are used to simulate three complex learning activities, such as learning states under different supervision levels, learning states based on levels of interest, and the effect of preview and review on memory behaviors according to the PQ4R (Preview, Question, Read, Reflect, Recite, Review) strategy that has rarely been reported. [37][38][39] This work of doping CDs not only improves the electrical performance of memristors, but also facilitates the development of artificial neural systems. [40][41][42]…”
Section: Introductionmentioning
confidence: 99%